artikel Ilmiyah PELESTARIAN MOTIF BATIK WRINGIN LAWANG DALAM UPAYA MENGENALKAN DAN MELESTARIKAN BUDAYA MAJAPAHIT DI KABUPATEN MOJOKERTO: Pendekatan Budaya dan Strategi Pengembangan Kreatif Masyarakat Lokal dalam Konteks Warisan Budaya Takbenda - Mustaqim, Moh. mustaqim (LP3M IAI Al-Qolam, 2025)
The preservation of the Wringin Lawang Batik motif as a means to introduce Majapahit culture in Mojokerto. The background of this research is based on the importance of preserving the Majapahit cultural heritage which is the historical identity of the Trowulan area, one of the centers of the glory of the Majapahit kingdom. The Wringin Lawang Batik motif is inspired by the architectural form of the Wringin Lawang Gate, a symbol of past greatness and glory, thus having high historical and philosophical value. The focus of this research is to understand the symbolic meaning and cultural values ​​contained in the batik motif and examine the various preservation efforts undertaken by craftsmen and related parties. The research approach uses a qualitative approach with a theoretical basis for the preservation of local culture and identity, which emphasizes the importance of cultural sustainability through adaptation and innovation without losing its original value. Data collection methods are carried out through in-depth interviews and direct observation of batik craftsmen, cultural figures, and local governments involved in the preservation program. The results of the study indicate that the Wringin Lawang Batik motif is not just a work of art, but also an educational medium that introduces the history of Majapahit to local communities and tourists. Preservation efforts are carried out through collaboration between artisans, the local government, and local communities, including training, cultural festivals, and batik tourism promotions. In conclusion, the preservation of the Wringin Lawang batik motif plays a crucial role in strengthening Mojokerto's cultural identity while sustainably preserving the legacy of the Majapahit civilization.